High Tau expression correlates with reduced invasion and prolonged survival in Ewing sarcoma - Cidre-Aranaz, Florencia; Magrin, Claudia; Zimmermann, Malenka; Li, Jing; Baffa, Annalisa; Ciccaldo, Matteo; Hartmann, Wolfgang; Dirksen, Uta; Sola, Martina; Paganetti, Paolo; Grünewald, Thomas G. P.; Papin, Stéphanie (Cell death discovery, 2025)
The microtubule-associated protein Tau (encoded by the MAPT gene) is linked to a family of neurodegenerative disorders defined as tauopathies, which are characterized by its brain accumulation in neurofibrillary tangles and neuropil threads. Newly described Tau functions comprise DNA protection, chromatin remodeling, p53 regulation and cell fate modulation, suggesting a role of Tau in oncogenesis. Bioinformatic-supported characterization of Tau in cancer reveals robust expression in bone cancer cells, in particular Ewing sarcoma (EwS) cell lines. EwS is an aggressive cancer caused by a fusion of members of the FET and ETS gene families, primarily EWSR1::FLI1. Here we found that MAPT is a EWSR1::ETS target gene and that higher Tau expression in EwS cells inhibited their migratory and invasive behavior, consistent with a more immobile and proliferative phenotype observed in EwS. Indeed, we report that high Tau expression is associated with improved overall survival of EwS patients. We also show that the sessile but proliferative phenotype of EWSR1::ETS-high cells may result from a modulatory role of Tau on focal adhesion to extracellular matrix proteins. Our data highlight the utility of determining Tau expression as a prognostic factor in EwS as well as the opportunity to target Tau expression as an innovative EwS therapy.
Gesehen am 05.11.2025